2014
DOI: 10.1159/000358219
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Blood-Cerebrospinal Fluid Barrier Dysfunction and the Therapeutic Effect in Tuberculous Meningitis Patients

Abstract: Objective: To explore the correlation of blood-cerebrospinal fluid (CSF) barrier (BCB) dysfunction with the therapeutic effect of antitubercular agents and their resistance, hoping to provide theoretical evidence for improvement of the therapeutic effect. Methods: Albumin in CSF and serum was assayed by IMMAGE. The CSF/serum albumin ratio (QALB) was used to evaluate the permeability of the BCB. Real-time fluorescence quantitative PCR was used to detect the amount of Mycobacterium tuberculosis DNA, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Thus, our results showed that PN-positive patients might have more serious BCB dysfunction and weak immune function. A previous study showed that the CSF/serum albumin ratio in patients with tuberculous meningitis who recovered was higher than that in patients who experienced a progress of illness, which may have been caused by weakening of the treatment effect due to hindrance of the drug delivery by the BCB [26]. Our observations showed that PN-positive CM patients experienced worse treatment response at week 2 and were more likely to have unfavorable clinical outcome.…”
Section: Discussionmentioning
confidence: 46%
“…Thus, our results showed that PN-positive patients might have more serious BCB dysfunction and weak immune function. A previous study showed that the CSF/serum albumin ratio in patients with tuberculous meningitis who recovered was higher than that in patients who experienced a progress of illness, which may have been caused by weakening of the treatment effect due to hindrance of the drug delivery by the BCB [26]. Our observations showed that PN-positive CM patients experienced worse treatment response at week 2 and were more likely to have unfavorable clinical outcome.…”
Section: Discussionmentioning
confidence: 46%
“…In a study on 83 patients with TBM, Q alb correlated with severity of disease and leucocyte counts. The patients with elevated Q alb had drug resistance [14]. This study, however, did not evaluate Q alb relationship with cytokines and MRI changes.…”
Section: Outcomementioning
confidence: 92%
“…The infraction in TBM is usually deep seated and smaller in size. Intra parenchymal tuberculoma reveals perilesional BBB abnormality revealing ring or disc enhancement on CT or MRI scan [14,41]. The association of basal exudates with Q alb suggests focal breach of B-CSF barrier.…”
Section: Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…Another important barrier of the CNS, especially for systemic treatment of LM, is the BCSFB [59,60] (Fig. 2).…”
Section: Blood-csf Barrier (Bcsfb)mentioning
confidence: 99%